The Control of Fluxes of Electric Power in Networks by Means of Phase-switching Booster Transformers - Govorov F.P.; Govorov V.F.; Romanova T.I. (Problems of the Regional Energetics)
roblems of increasing the efficiency of the operation of electrical networks based on the utilization of booster transformers (BT) with electronic control, applied on the base of active elements in smart electric grids of power systems and giving the function of automatic correction of the parameters of the network, assuring the conditions of optimal common operation are studied in the paper. The mathematic model of the processes in the electric networks with booster transformer has been developed; the opportunity of control by means of the phase-switching BT for power fluxes in the networks has been established. It has been shown that for the groups of switching the windings 1-5 of BT occurs additional consumption of power from the supply network, but for the groups 7-11 its recuperation to the load network. Respectively, switching the windings of BT to the group 1-5 assures the shift of load current to the direction of lag, but in the case of switching to the group 7-11 – towards the outrunning. Wherein, for the groups of switching 10-11 and 1-2 one can observe the increasing of the voltage at the output of BT, but for the groups 7-8 and 4-5 it is decreasing. Based on the analysis of the results of research the diagram and constructive models of the transformer have been proposed. The quasi-stationary and transient regimes were investigated and the conditions of reliable operation at these the regimes have been determined. The ways for increasing the efficient common operation for the transformer and network in the case of switching the thyristors into the circuit of the primary winding of the transformer have been proposed.